2022
DOI: 10.3390/mti6070058
|View full text |Cite
|
Sign up to set email alerts
|

The Appraisal Principle in Multimedia Learning: Impact of Appraisal Processes, Modality, and Codality

Abstract: This paper presents two experiments examining the influences of media-specific appraisal and attribution on multimedia learning. The first experiment compares four different versions of learning material (text, text with images, animation with text, and animation with audio). Results reveal that the attributed type of appraisal, (i.e., the subjective impression of whether a medium is easy or difficult to learn with) impacts invested mental effort and learning outcomes. Though there was no evidence for the moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The Expectancy-Value Theory of Eccles and Wigfield [39] also showed that task value, perceived self-efficacy, anticipated effort, and task difficulty play a major role in learners' motivation. Confronted with a learning task, individuals weigh the costs-invested time and effort-against the values of task completion [40,41]. Whether learners feel capable of solving a task depends on their prior knowledge and their academic self-concept.…”
Section: Motivationmentioning
confidence: 99%
“…The Expectancy-Value Theory of Eccles and Wigfield [39] also showed that task value, perceived self-efficacy, anticipated effort, and task difficulty play a major role in learners' motivation. Confronted with a learning task, individuals weigh the costs-invested time and effort-against the values of task completion [40,41]. Whether learners feel capable of solving a task depends on their prior knowledge and their academic self-concept.…”
Section: Motivationmentioning
confidence: 99%